1991
DOI: 10.1515/cogl.1991.2.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Limits to attention: A cognitive theory of island phenomena

Abstract: AbsiraclSyntactic Island constraints are generally viewed äs paradigmatic evidence for the autonomy of syntax. However, the existence ofexceptions has been known for some time. Close examination reveals that these exceptional phenomena resist purely syntactic explanations, requiring insteadan account in terms of semanüc relations like attribution, various kinds of semantic framing ejfects, and discourse variables like topic and focus. It will be argued that the syntactic and extrasyntactic factors which limit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(69 citation statements)
references
References 3 publications
0
68
0
1
Order By: Relevance
“…This is not unexpected. Pesetsky (1989) has shown that Dlinking plays a major role in ameliorating extraction out of weak islands; a similar observation is reported inter alia in Chung and McCloskey (1983);Chomsky (1986); Cinque (1990); Hegarty (1990); Deane (1991); Pollard and Sag (1994); Comorovski (1996) Brought to you by | Periodicals Section, Albert Sloman Libr. Authenticated Download Date | 7/22/15 11:00 AM (2012).…”
Section: Internal Properties Of the Extracteementioning
confidence: 56%
“…This is not unexpected. Pesetsky (1989) has shown that Dlinking plays a major role in ameliorating extraction out of weak islands; a similar observation is reported inter alia in Chung and McCloskey (1983);Chomsky (1986); Cinque (1990); Hegarty (1990); Deane (1991); Pollard and Sag (1994); Comorovski (1996) Brought to you by | Periodicals Section, Albert Sloman Libr. Authenticated Download Date | 7/22/15 11:00 AM (2012).…”
Section: Internal Properties Of the Extracteementioning
confidence: 56%
“…5 The strength of conclusions that can be drawn from a lack of evidence has raised concerns, particularly because some island domains have been argued to themselves constitute complex processing environments, whether a dependency is present or not (e.g. Deane 1991, Kluender 2004. Therefore null findings in island processing are liable to alternative interpretations that are unrelated to the parser's interaction with the grammar.…”
Section: Islandsmentioning
confidence: 99%
“…Il existe une littérature fournie consacrée aux extractions hors de syntagme nominal (SN) sujet (Deane 1991, Sabel 2002, Chaves 2013 qui semble problématique dans certaines langues, comme l'anglais 2 . Il existe plusieurs études empiriques sur l'anglais et sur d'autres langues (Polinsky et al 2013, Sprouse et al 2015, mais nous n'avons pas connaissance d'études similaires réalisées sur le français.…”
Section: Introductionunclassified